The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21608/svuijas.2021.69758.1097
|View full text |Cite
|
Sign up to set email alerts
|

Ratooning ability and its relationship among yield, quality and lesser sugarcane borer (Chilo agamemnon Bels.) in sugarcane germplasm

Abstract: This study was conducted at El-Mattana Agricultural Research Station, Luxor Governorate, Egypt (latitude of 25.17° N and longitude of 32. 33°E) on three sugar crop cycles 2017/18 (plant cane crop), 2018/19 (the first ratoon) and 2019/20 (the second ratoon) to screen sugarcane genotypes for yield, quality and borer resistance, also estimates the relationship among agronomical and pathological traits based on principal components biplot analysis. Results revealed that significant differences among sugarcane geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…For instance, in a study of Egyptian sugarcane across three crop years, yield (a combination of biomass and sugar production) differed with plant age and variety, as did susceptibility to the lesser sugarcane borer ( Chilo agamemnon Błeszyński; Lepidoptera: Crambidae) 109 . This study found that the varieties with the greatest borer damage in plant cane were not the same varieties that had the most damage in the first or second ratoons 109 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, in a study of Egyptian sugarcane across three crop years, yield (a combination of biomass and sugar production) differed with plant age and variety, as did susceptibility to the lesser sugarcane borer ( Chilo agamemnon Błeszyński; Lepidoptera: Crambidae) 109 . This study found that the varieties with the greatest borer damage in plant cane were not the same varieties that had the most damage in the first or second ratoons 109 …”
Section: Discussionmentioning
confidence: 89%
“…The age‐associated differences in herbivory between plant cane and ratoons seen in other studies may be due, in part, to changes in plant physiology and related defenses such as stalk density, biochemical composition, and ripening rate (sugar accumulation) of particular varieties grown in those countries 107,108 . For instance, in a study of Egyptian sugarcane across three crop years, yield (a combination of biomass and sugar production) differed with plant age and variety, as did susceptibility to the lesser sugarcane borer ( Chilo agamemnon Błeszyński; Lepidoptera: Crambidae) 109 . This study found that the varieties with the greatest borer damage in plant cane were not the same varieties that had the most damage in the first or second ratoons 109 …”
Section: Discussionmentioning
confidence: 99%